Gelam Honey Inhibits the Production of Proinflammatory, Mediators NO, PGE(2), TNF-α, and IL-6 in Carrageenan-Induced Acute Paw Edema in Rats - Hussein, Saba Zuhair (Hindawi Publishing Corporation, 2012)
Natural honey is well known for its therapeutic value and has been used in traditional medicine of different cultures throughout the world. The aim of this study was to investigate the anti-inflammatory effect of Malaysian Gelam honey in inflammation-induced rats. Paw edema was induced by a subplantar injection of 1% carrageenan into the rat right hind paw. Rats were treated with the nonsteroidal anti-inflammatory drug (NSAID) Indomethacin (10 mg/kg, p.o.) or Gelam honey at different doses (1 or 2 g/kg, p.o.). The increase in footpad thickness was considered to be edema, which was measured using a dial caliper. Plasma and paw tissue were collected to analyze the production of inflammatory mediators, such as NO, PGE(2), TNF-α, and IL-6, as well as iNOS and COX-2. The results showed that Gelam honey could reduce edema in a dose-dependent fashion in inflamed rat paws, decrease the production of NO, PGE(2), TNF-α, and IL-6 in plasma, and suppress the expression of iNOS, COX-2, TNF-α, and IL-6 in paw tissue. Oral pretreatment of Gelam honey at 2 g/kg of body weight at two time points (1 and 7 days) showed a significantly decreased production of proinflammatory cytokines, which was similar to the effect of the anti-inflammatory drug Indomethacin (NSAID), both in plasma and tissue. Thus, our results suggest that Gelam honey has anti-inflammatory effects by reducing the rat paw edema size and inhibiting the production of proinflammatory mediators. Gelam honey is potentially useful for treating inflammatory conditions.